Strain-dependent differences in corticolimbic processing of aversive or rewarding stimuli - Andolina, Diego; Puglisi-Allegra, Stefano; Ventura, Rossella (Frontiers in Systems Neuroscience, 2015)
Aberrations in the elaboration of both aversive and rewarding stimuli characterize several psychopathologies including anxiety, depression and addiction. Several studies suggest that different neurotrasmitters, within the corticolimbic system, are critically involved in the processing of positive and negative stimuli. Individual differences in this system, depending on genotype, have been shown to act as a liability factor for different psychopathologies. Inbred mouse strains are commonly used in preclinical studies of normal and pathological behaviors. In particular, C57BL/6J (C57) and DBA/2J (DBA) strains have permitted to disclose the impact of different genetic backgrounds over the corticolimbic system functions. Here, we summarize the main findings collected over the years in our laboratory, showing how the genetic background plays a critical role in modulating amminergic and GABAergic neurotransmission in prefrontal-accumbal-amygdala system response to different rewarding and aversive experiences, as well as to stress response. Finally, we propose a top-down model for the response to rewarding and aversive stimuli in which amminergic transmission in PFC controls accumbal and amygdala neurotransmitter response.